2021
DOI: 10.1016/j.jinf.2021.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Initial viral load and decay kinetics of SARS-CoV-2 lineage B.1.1.7 in the upper respiratory tract of adults and children

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The elevated viral titers with Alpha-infections compared with WT were expected, due to the increased transmissibility in the variant via enhanced receptor binding affinity due to the N501Y mutation. 7 , 15 Furthermore, viral loads have shown to be higher in Alpha-variant infections than non-VOC strains in other studies, 40 , 41 , 42 , 43 , 44 which appeared to be more evident in adults compared with children, 43 supporting our observations.…”
Section: Discussionsupporting
confidence: 90%
“…The elevated viral titers with Alpha-infections compared with WT were expected, due to the increased transmissibility in the variant via enhanced receptor binding affinity due to the N501Y mutation. 7 , 15 Furthermore, viral loads have shown to be higher in Alpha-variant infections than non-VOC strains in other studies, 40 , 41 , 42 , 43 , 44 which appeared to be more evident in adults compared with children, 43 supporting our observations.…”
Section: Discussionsupporting
confidence: 90%
“…The SARS‐CoV‐2 variant involved in the outbreaks was determined by whole‐genome sequencing at the Foundation for the promotion of Health and Biomedical Research of the Valencian Community (FISABIO), as previously reported. 8 …”
Section: Methodsmentioning
confidence: 99%
“…SARS‐CoV‐2 viral loads in NP were estimated using the AMPLIRUN® TOTAL SARS‐CoV‐2 RNA Control (Vircell SA), 6 and reported as copies/ml throughout the study. The SARS‐CoV‐2 variant involved in the outbreaks was determined by whole‐genome sequencing at the Foundation for the promotion of Health and Biomedical Research of the Valencian Community (FISABIO), as previously reported 8 …”
Section: Methodsmentioning
confidence: 99%
“…Although adult data have reported higher viral loads in Alpha VoC samples as measured by Ct and genomic copies, in a retrospective study conducted in Spain, a higher SARS-CoV-2 load was detected in Alpha-infected adults compared to other variants, no such differences were detected in children. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Although adult data have reported higher viral loads in Alpha VoC samples as measured by Ct and genomic copies, in a retrospective study conducted in Spain, a higher SARS-CoV-2 load was detected in Alpha-infected adults compared to other variants, no such differences were detected in children. 10 Although ddPCR has characteristics that make it analytically superior to RT-PCR, given the capital equipment costs and timeconsuming protocol, we are not proposing that it replace RT-PCR as the standard of care during the COVID-19 pandemic. However, the data we report inform our knowledge about viral loads and RT-PCR test accuracy in our study population.…”
Section: Discussionmentioning
confidence: 99%